Perioperative Risk Factors Associated With Acute Kidney Injury in Patients After Brain Tumor Resection. Issue 1 (January 2022) - Li, Jiaxin; Zhao, Yan; Yan, Xiang; Li, Ruowen; Zhang, Xingyue; Zeng, Min; Dong, Jia; Li, Shu; Peng, Yuming; Han, Ruquan
Abstract : Background: Acute kidney injury (AKI) is a serious complication after surgery. The aim of this study is to identify risk factors for postoperative AKI in patients undergoing brain tumor surgery. Methods: This single-center, retrospective, matched case-control study included patients undergoing elective brain tumor surgery between January 2016 and December 2018 at Beijing Tiantan Hospital, Capital Medical University, China. Patients developing postoperative AKI were compared with controls without AKI matched by age, sex, and date of surgery in a ratio of 1:3. AKI was defined using the Kidney Disease Improving Global Outcomes criteria. Results: A total of 9933 patients were identified for review, of which 115 (1.16%) developed AKI; 345 matched patients were included in the control group. AKI occurred most commonly within the first 24 hours (41/97, 42.3%) and 48 hours (33/94, 35.1%) after surgery. Preoperative administration of mannitol (odds ratio [OR], 1.64; 95% confidence interval [CI], 1.04-2.60; P = 0.034), American Society of Anesthesiologists physical status III or higher (OR, 5.50; 95% CI, 2.23-13.59; P <0.001), preoperative blood glucose (OR, 2.53; 95% CI, 1.23-5.22; P =0.012), craniopharyngioma (OR, 8.96; 95% CI, 3.55-22.63; P <0.001), nonsteroidal anti-inflammatory drug administration (OR, 3.74; 95% CI, 1.66-8.42; P <0.001), and intraoperative hypotension (OR, 2.13; 95% CI, 1.21-3.75; P =0.009) were independent risk factors for postoperative AKI. Conclusion: Multiple factors, including preoperative administration of mannitol, are independently associated with the development of postoperative AKI in patients undergoing brain tumor surgery. Abstract : Supplemental Digital Content is available in the text.